Estimation of Cellular Content in Second-Generation Solid Fibrin Concentrates (PRFs) - Michela Crisci; Alessandro Crisci (Cutting Edge Research in Biology Vol. 4, 2023)
We performed a study to evaluate the amount of Platelets and Leukocytes in a second-generation solid platelet concentrates in terms of Sensitivity, Specificity, Positive Predictive Value (VP+), Negative Predictive Value (VP-), False Negative Proportion, and False Positive Proportion of our Statistical Method. Blood was collected in anticoagulant-free PET tubes with silica for clot production and PRF membranes. The membranes and clots produced were examined. In a previous work, the authors, starting from the results obtained in Kitamura’s work, wanted to develop an easier and inexpensive system to calculate the exact amount of platelets and leukocytes contained in PRF, compared to the one present in whole blood, starting from a simple "haemochromocytometric examination". In this study, the authors have evaluated the Sensitivity, Specificity, Positive Predictive Value (VP+), Negative Predictive Value (VP-), False Negative Proportion, and False Positive Proportion of the "Statistical Method". Using the Statistical Method, we have this result by reducing by 34.12% (±28.2) the value of leukocytes obtained from the CBC examination. We obtained the value of leukocytes contained in the PRF membrane by t-PA digestion and by reducing by 15.12% (±24.87) the value of platelets obtained by the same method, we have reached the value contained in solid platelet concentrates by t-PA digestion. The proposed method proved a Se=0.75; Sp=0.86; VP+=0.75; VP-=0.86 for platelet counts, Se=0.47; Sp=0.66; VP+=0.80; VP-=0.30 for leukocyte counts. Conclusion: Our study tried to standardize the PRF preparation procedure by validating a statistical system to calculate the exact amount of platelets and leukocytes in second-generation solid platelet concentrates, making it easy to evaluate individual PRF arrays on time in the clinical setting. The Statistical method compared to the digestive method with t-PA for leukocyte and platelet counts proved to be equally valid for platelets, but not in the same way for leukocytes.